Dampak Program Bantuan Sepeda Motor Bercoolbox Terhadap Pendapatan Pedagang Ikan Keliling Di Provinsi Gorontalo - Sitti Sabariah Machmud; Mahludin Baruwadi; Azis Salam (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
The objectives of this study are 1) To find out the impact of the coolbox motor vehicle assistance program on increasing the income of traveling fish traders in Gorontalo Province, 2) Analyzing the level of motivation to run a mobile fish trader after receiving coolbox motorized vehicle assistance in Gorontalo Province and 3) Determine the strategy for developing vehicle assistance programs motorized coolbox in Gorontalo Province. This research was conducted in Gorontalo City, Gorontalo Regency and Bone Bolango Regency from March to May 2019 with a total sample of 68 traveling fish traders who received motorbike box assistance. The research method used was a survey method. Analysis of the data used is the average difference test (t-test), a qualitative descriptive analysis based on Maslow's theory referring to a Likert scale, and a SWOT analysis. The results showed that motorbike box assistance to traveling fish traders in Gorontalo Province had a positive impact. This can be seen from the increase in income and increased motivation from itinerant fish traders. And based on the results of the SWOT analysis, that the internal conditions of the Organization in this case the Gorontalo Provincial Government used a survival strategy, controlling internal performance. This strategy is maintained while continuing to improve itself and still needs a lot of support and guidance so that the fisheries sector can make a significant contribution in regional development and other assistance program development strategies.